2017
DOI: 10.1186/s12882-017-0547-0
|View full text |Cite
|
Sign up to set email alerts
|

Dementia is a risk factor for major adverse cardiac and cerebrovascular events in elderly Korean patients initiating hemodialysis: a Korean national population-based study

Abstract: BackgroundDementia is common in end-stage renal disease (ESRD) patients on hemodialysis (HD) and is associated with worse outcomes. This study aimed to investigate the risk of major adverse cardiac and cerebrovascular event (MACCE) in elderly patients with dementia initiating HD.MethodsUsing the database from the Health Insurance Review & Assessment Service, we analyzed 10,171 patients aged 65 years or older who had initiated dialysis from 2005 to 2008. MACCE was defined as a composite outcome of all-cause mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
3
1
Order By: Relevance
“…These findings are consistent with those of recent studies, which reported that the presence of dementia before dialysis increased the risk of postdialysis mortality by 19% to 30% [18,19]. Multiple factors, such as increased cardiac and cerebrovascular risks [19], frailty [14,20], impeding treatment adherence [21], and comorbidities [22], may contribute to post-ESKD mortality in dementia. Interestingly, dementia in the subgroup with comorbid CVA or severe behavioral disorders was not significantly associ-…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those of recent studies, which reported that the presence of dementia before dialysis increased the risk of postdialysis mortality by 19% to 30% [18,19]. Multiple factors, such as increased cardiac and cerebrovascular risks [19], frailty [14,20], impeding treatment adherence [21], and comorbidities [22], may contribute to post-ESKD mortality in dementia. Interestingly, dementia in the subgroup with comorbid CVA or severe behavioral disorders was not significantly associ-…”
supporting
confidence: 92%
“…Although the severity of dementia was not investigated in this study, it is surprising that more than 8% of patients with ESKD exhibit dementia at the time of hemodialysis initiation in South Korea. A previous study based on the Korean Health Insurance Review and Assessment Service database between 2005 and 2008 showed that 3.0% of patients aged >65 years had dementia at the time of hemodialysis initiation [19]. The lower prevalence of dementia compared to that in our study is possibly due to underdiagnosis during the coding procedure in the previous study.…”
contrasting
confidence: 59%
“…HIRA data are anonymized to protect the privacy of individuals, and the HIRA provides individual numbers for researches that replace the social security numbers. The data are widely used in various fields of medical research [ 20 , 27 , 28 ]. The study protocol was approved by the Institutional Review Board of Samsung Medical Center (No.…”
Section: Methodsmentioning
confidence: 99%
“…The data are widely used in various fields of medical research. 20,27,28 The study protocol was approved by the Institutional Review Board of Samsung Medical Center (No. 2019-04-022).…”
Section: Data Sourcementioning
confidence: 99%
“…All-cause mortality is the most objectively measurable surrogate endpoint because it has minimal chance of being affected by bias in patient selection, missing data, or misclassification of the cause of death [9]. Although it is ideal to merge NHIS data with that from Statistics Korea to investigate the time of death as well as the cause of death [10][11][12], analysis of all-cause mortality is feasible based on mortality information from the NHIS database. In the Korean HD population, alternatively, studies on all-cause mortality have been conducted using HIRA data by defining all-cause mortality as death where no claims were made for a certain period of time such as 30 days, 90 days, or more than 180 days [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%